Antimicrobial Activity of Melinjo Seed and Peel Extract (Gnetum gnemon) Against Selected Pathogenic Bacteria - ADOLF JAN NEXSON PARHUSIP; AZIS BOING SITANGGANG (Indonesian Society for microbiology, 2011)
Melinjo (Gnetum gnemon L.) is an Indonesian native plant which has not been widely accepted due to its limited utilization. Mainly, melinjo is consumed as an ingredient to make a vegetable dish or as raw material of ‘emping’. The purpose of this research was to study the antimicrobial activity of the melinjo seed extract and melinjo peel extract. In this study, extraction from melinjo seed and peel was conducted by maceration using three kinds of solvent: ethanol, ethyl acetate and hexane for 24 h at room temperature. The results showed that none of the melinjo extracts (concentration from 5% - 25% w/v) could inhibit the growth of Aspergillus flavus IPBCC 88.030; whereas for Bacillus cereus ATCC 10876, Staphylococcus aureus ATCC 25953, and Enterobacter aerogenes ATCC 13048 there was efficient inhibition by 5% (w/v) of melinjo seed-ethanol extract. The minimal inhibitory concentration (MIC) value of melinjo extract was ranged from 0.26 μg mL-1 to 1.46 μg mL-1, whilst the minimal bactericidal concentration (MBC) value was ranged from 1.02 μg mL-1 to 6.04 μg mL-1. The inhibitory capacity of extract had a similar level as compared to 10 ppm penicillin G on B. cereus ATCC 10876 as well as on S. aureus ATCC 25953. Furthermore, as compared to 10 ppm streptomycin, the inhibitory capacity of the extract was equal for the all tested bacteria. Cell wall deformation was observed using SEM, and confirmed by the presence of ions (Ca2+ and K+) outside of the cells, detected by means of AAS.